Rough sets. International Joint Conference, IJCRS 2017, Olsztyn, Poland, July 3-7, 2017, Proceedings /: International Joint Conference, IJCRS 2017, Olsztyn, Poland, July 3-7, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available